2014
DOI: 10.12816/0018907
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Conceptual Framework for Knowledge Sharing Behavior by Considering Emotional , Social and Cognitive Intelligence Competencies

Abstract: Present age is called knowledge economy age. Hence, many organizations think about using tools like knowledge management for their survival. Human activities such as knowledge sharing among organizational members are the basis of knowledge management process in organizations. In many scientific articles, the impact of human traits such as intelligent on knowledge is discussed. Present study is a descriptive survey-type. It aims at studying the impact of employees' intelligent components on knowledge sharing be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Similarly, Goh and Lim (2014) found that emotional intelligence influences one's willingness to share his or her knowledge in the context of MNCs in Malaysia. Some more studies confirmed the positive impact of emotional intelligence on knowledge sharing (Abzari et al, 2014;Arabshahi et al, 2013;Arakelian et al, 2013;Obermayer-Kov acs et al, 2015;Naz et al, 2019). A few studies were also conducted to test the significance of emotional intelligence dimensions towards knowledge sharing.…”
Section: Emotional Intelligencementioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, Goh and Lim (2014) found that emotional intelligence influences one's willingness to share his or her knowledge in the context of MNCs in Malaysia. Some more studies confirmed the positive impact of emotional intelligence on knowledge sharing (Abzari et al, 2014;Arabshahi et al, 2013;Arakelian et al, 2013;Obermayer-Kov acs et al, 2015;Naz et al, 2019). A few studies were also conducted to test the significance of emotional intelligence dimensions towards knowledge sharing.…”
Section: Emotional Intelligencementioning
confidence: 89%
“…For example, Arakelian et al (2013) found that selfawareness, social awareness and relationship management dimensions of emotional intelligence positively impacted knowledge sharing. Likewise, Abzari et al (2014) found that self-management and self-awareness positively impacted knowledge sharing behaviour. Similarly, the empirical studies in Indian context also showed a positive influence of emotional intelligence on overall knowledge sharing (Ansari and Malik, 2017;Tamta and Rao, 2017;Priyadarshi and Premchandran, 2019).…”
Section: Emotional Intelligencementioning
confidence: 96%
See 1 more Smart Citation
“…Studies have revealed a relation between personality traits and knowledge sharing behavior: Lee & Al-Hawamdeh (2002) found that employees' communication style and motivation influenced their knowledge sharing behavior. Another example is Abzari, Shahin, & Abasaltian (2014) whose study results indicate that emotional and social intelligence have a significant impact on knowledge sharing behavior. The relation between knowledge sharing and personality traits will be discussed further in this paper.…”
Section: Personality Traits and Workplace Behaviormentioning
confidence: 99%
“…People may keep themselves out of a knowledge exchange if they feel they can beneit more by hoarding their knowledge rather than by sharing it (Davenport and Prusak, 1998). Abzari et al (2014) have identiied that social and emotional competence have an impact on employees' knowledge sharing behaviour. Also, the effect of emotional intelligence competency has been proved to be positive and signiicant on knowledge sharing behaviour.…”
Section: Knowledge Sharingmentioning
confidence: 99%